Cytocompatibility of Biodentine and iRoot FS with human periodontal ligament cells: an in vitro study. (6th February 2018) - Luo, T.; Liu, J.; Sun, Y.; Shen, Y.; Zou, L.
Abstract: Aim: To evaluate the cytocompatibility of Biodentine and iRoot FS with human periodontal ligament cells (hPDLCs). Methodology: Human periodontal ligament cells were characterized by flow cytometry and immunocytochemical analysis. Human periodontal ligament cell adhesion was assessed by scanning electron microscopy at day 3; proliferation by live/dead assay at days 1, 3 and 7; and osteogenic differentiation by alkaline phosphatase (ALP) activity staining, ALP quantification analysis and qRT‐PCR at days 7 and 14. Data were analysed withanova and independent sample t‐ tests with SPSS 21.0. Results: Both iRoot FS and Biodentine increased the adhesion of hPDLCs at day 3. Compared to Biodentine, iRoot FS positively increased hPDLC proliferation on days 3 ( P = 0.03) and 7 ( P = 0.00). Osteogenic marker ALP was observed consistently in all samples, with iRoot FS having significantly higher ALP activity at day 14 ( P = 0.00). Compared with Biodentine, iRoot FS significantly increased the mRNA level of ALP, COL1 and Runx2, and OCN increased only on day 14 ( P < 0.05). Conclusions: iRoot FS had a positive effect on the adhesion, proliferation and biomineralization of hPDLCs compared with Biodentine.